Teaching Program Based on (ChatGPT) and Its Effectiveness in Developing Reading Comprehension Skills for English Language Students at University - Al-Otaibi, Mai; Al-Homidhi, Khalid Mohamed (International Journal of Language and Literary Studies, 2025)
The current study aimed at building a teaching program based on (ChatGPT) to develop reading comprehension skills and evaluate its effectiveness in developing reading comprehension skills among undergraduate English language students at university. The study applied the descriptive analytical approach by building a list of reading comprehension skills in the English language (a questionnaire) designed for this purpose, and used the experimental method with a semi-experimental design by using (a pre- and post-reading comprehension skills test). The study's sample consisted of (60) female students divided into two groups: a control group consisting of (30) students and an experimental group consisting of (30) students. The study revealed the effectiveness of the ChatGPT-based teaching program in developing literal, deductive, aesthetic, creative, and critical comprehension skills among the students in the experimental group. The study recommended conducting training courses for faculty members and students on how to use (ChatGPT) and organizing workshops to raise awareness among faculty members about the importance of applying (ChatGPT) in teaching English language courses. Additionally, distribute informational brochures to both managers and supervisors to enhance the role of faculty members in utilizing other artificial intelligence applications.